Quantitative analysis of powdered caffeine products purchased from the Internet using liquid chromatography–quadrupole time-of-flight mass spectrometry. (20th April 2016) - Beauchamp, Gillian A.; Lin, Thomas; Zeng, William Z. D.; Hendrickson, Robert G.; Gerona, Roy
ABSTRACT: Context : Powdered caffeine is sold on the Internet as a supplement. Severe toxicity and fatalities have been reported with use, but it is unclear if this toxicity was due to excessive dosing, mislabeled products, or adulterant stimulants. Our objective was to analyze the contents of commercially available powdered caffeine products in order to assess product purity and presence of additional ingredients, contaminants, or adulterants which may contribute to toxicity.Methods : A sample of nine powdered caffeine products was purchased from the Internet. Two sample replicates of each caffeine product were analyzed. Liquid chromatography–quadrupole time-of-flight mass spectrometry (LC-QTOF/MS) was used to identify and quantify substances in the purchased products and purity of the compounds were calculated.Results : Comparison of actual mass versus labeled mass of caffeine demonstrated a mean purity of 88.25% (SD 13.41%) and median purity of 90.1%. The products studied contained 1.6–5.3 g per teaspoon. Labeling on these products had limited instructions regarding how to measure the recommended dose.Conclusions : Powdered caffeine products that are readily available on the Internet contained relatively pure caffeine with no additional detected stimulants. High purity, small serving size, and lack of clear dosing instructions may place users at risk of toxicity.